VOCATIONAL PREFERENCES OF VILLAGE YOUTH AFTER JUNIOR HIGH SCHOOL - PIETRUK, Witold (Trends in education, 2011)
The article presents the results of a questionnaire undertook among the third-year students of junior high school from Brzeg area (Opole Province). The aim of the research was to specify vocational preferences of the youth from village schools as well as to show the types of school and occupations most often chosen by them. Furthermore, the preferences of students that have an influence on choice of their further education are presented in this article.
Keywords: vocational preferences; third-year students of junior high school from village area; choosing appropriate school and occupation.